2021
DOI: 10.3390/ijerph18052341
|View full text |Cite
|
Sign up to set email alerts
|

Variety of Surgical Guides and Protocols for Bone Reduction Prior to Implant Placement: A Narrative Review

Abstract: Edentulism and terminal dentition are still considered significant problems in the dental field, posing a great challenge for surgical and restorative solutions especially with immediate loading protocols. When the implant placement is planned immediately after extraction with irregular bone topography or there is an un-leveled alveolar ridge topography for any other reason, bone reduction may be required to level the alveolar crest in order to create the desired bone architecture allowing for sufficient bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In recent years, some studies have reported that at 4–8 weeks after tooth extraction, a large amount of the alveolar crest has not been absorbed [ 24 , 25 ]. In order to prevent excessive absorption of alveolar bone and obtain a good aesthetic effect later on, early implantation is encouraged [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies have reported that at 4–8 weeks after tooth extraction, a large amount of the alveolar crest has not been absorbed [ 24 , 25 ]. In order to prevent excessive absorption of alveolar bone and obtain a good aesthetic effect later on, early implantation is encouraged [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The flap has a flange that extends onto the slope of the ridge, keeping it away from the osteotomy site and preventing it from falling back onto the surgical site. With this an assistant also visualizes the surgical site without interrupting the surgeon to guide for correct positioning and depth [2]. A small aperture is given on the occlusal side so that the pilot drill could be placed in accurate position from the buccal side rather than the occlusal side in cases when the patient has reduced mouth opening or when the implant has to be placed most posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of diagnostic and prosthetic planning information to the surgical phase is critical. Ideal Prerequisites-It should be rigid buccolingually, mesio distally and apico coronally in the correct position [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the improvement of medical technology, implant repair has become the preferred method for clinicians and patients to treat missing teeth [1,2]. The use of an implant guide plate can help achieve u n c o r r e c t e d p r o o f v e r s i o n accurate positioning in the operative process and guarantee the correct position, angle, and depth of the implant [3][4][5].…”
Section: Introductionmentioning
confidence: 99%